Removal of Multiple Contaminants from Water by Polyoxometalate Supported Ionic Liquid Phases (POM‐SILPs). Issue 6 (12th January 2017) - Herrmann, Sven; De Matteis, Laura; de la Fuente, Jesús M.; Mitchell, Scott G.; Streb, Carsten
Abstract: The simultaneous removal of organic, inorganic, and microbial contaminants from water by one material offers significant advantages when fast, facile, and robust water purification is required. Herein, we present a supported ionic liquid phase (SILP) composite where each component targets a specific type of water contaminant: a polyoxometalate‐ionic liquid (POM‐IL) is immobilized on porous silica, giving the heterogeneous SILP. The water‐insoluble POM‐IL is composed of antimicrobial alkylammonium cations and lacunary polyoxometalate anions with heavy‐metal binding sites. The lipophilicity of the POM‐IL enables adsorption of organic contaminants. The silica support can bind radionuclides. Using the POM‐SILP in filtration columns enables one‐step multi‐contaminant water purification. The results show how multi‐functional POM‐SILPs can be designed for advanced purification applications. Abstract : Pure and simple : Multi‐functional polyoxometalate supported ionic liquid phases (POM‐SILPs) can remove organic, inorganic, and microbial contaminants from water. Each POM‐SILP component targets one specific contaminant so that toxic heavy metals, radionuclides, organic dyes, and bacteria can be removed from water simultaneously.